(untitled) - Earl, Michael J. (New York, 1989)
Chapters suggest both why and how exploitation of IT should be connected to business strategy formulation, and examine some traditional problems of information systems management from this strategic perspective.
Keywords: Information resources management,Information technology,Công nghệ thông tin,Quản lý nguồn thông tin